The Face of Law Supremacy: A Media Content Analysis on Artalyta’s Luxurious Prison Case on The Jakarta Globe Newspaper - Rino Febri; Ariesa Lie (The Indonesian Journal of Communication Studies, 2010)
This research looks at the potrayal of the Indonesian government, particularly the law en- forcement institution that was responsible for the luxurious prison case of Artalyta and some other wealthy inmates. This issue came to surface when a sudden inspection was conducted by a newly established Judicial Mafia Eradication Task Force on Sunday, 10 January 2010 at Pondok Bambu Penitentiary. The discovery of the inspection was actually no big sudden as it has become a public secret. However, it still disgraced the image of the government since the media blew this issue up and eventually gained public’s attention. This research used a quantitative media content analysis method. This method used numbers as the basis of data interpretation and elaboration to the rel- evant theories. Precisely 53% of the total articles written contained unfavorable impressions of the Indonesian government. Government’s dishonest and corrupt were impressions appeared in the news. Nonetheless, some articles appeared favorable toward the Ministry of Justice and Human Rights as a result of strict action taken against corrupted officials.